Animal models for neuropsychiatric disorders: prospects for circuit intervention. (August 2017) - Kaiser, Tobias; Zhou, Yang; Feng, Guoping
Highlights: Complex disorders can be deconstructed into individual circuit defects. Depending on the circuit, defects may be reversible in adulthood. Emerging circuit- and gene-modulating technologies promise new interventions. Abstract : Monogenic animal models for psychiatric diseases have enabled researchers to dissect the relationship between certain candidate genes, neural circuit abnormalities, and behavioral phenotypes along development. Early reports of phenotypic reversal after genetic restoration in mouse models sparked hope that genetic defects do not damage circuits irreversibly in early-onset disorders. However, further studies have suggested that only some circuits exhibit this plasticity, while many others require proper gene function during development. This review focuses on what we have learned from a few evolutionarily conserved circuit–phenotype relationships and their developmental windows to illustrate their importance when considering intervention strategies.